A Long-Term Overview of Elasmobranch Fisheries in an Oceanic Archipelago: A Case Study of the Madeira Archipelago - Mafalda Freitas; Filipa Pinho-Duarte; Madalena Gaspar; Pedro Ideia; João Delgado; Sara C. Cerqueira; Ricardo Sousa (Fishes, 2025)
Elasmobranch species are considered a global conservation priority due to their susceptibility to fishing pressure. In the Madeira Archipelago, Northeastern Atlantic, most elasmobranch species are caught as bycatch in artisanal drifting longline fishery targeting scabbardfishes. All commercial elasmobranch landings carried out in this archipelago over three decades (1990–2020) were analysed, aiming to provide a reliable overview of Madeira’s elasmobranch fisheries and their evolution. A total of 2316 tonnes of elasmobranchs were landed during the study period, corresponding to approximately EUR 2.1 million in first-sale value. The most representative period occurred from 2003 to 2013, corresponding to 75.21% of the total elasmobranch landings. A general pattern of supply and demand was evident, with mean price values typically showing an inverse trend to landed tonnage. At the species level, Centrophorus squamosus appears as the dominant species, representing about 89% of the total elasmobranch species landed, followed by Prionace glauca, with approximately 3%. The high dominance of C. squamosus in the scabbardfish fishery raises significant ecological and management concerns, as this deep-water shark species is known for its vulnerability to overexploitation. Management measures currently in place need to be updated and ought to be based on studies on the type and size of hooks for each fishery, to ultimately infer about species-specific survival rates, as well as the fishing gears’ soak time. Moreover, studies on the enhancement of food supply through fisheries discards are still missing, even though it is highly likely that this input may alter the dynamics of marine food webs.

Molecular landscape of therapeutic deep eutectic systems selective toxicity towards colorectal cancer - Filipe Oliveira; Joana Pinto; Filipa Amaro; Joana Pereira; Inês Ferreira; Mário S. Diniz; Paula Guedes de Pinho; Ana Rita C. Duarte (Sustainable Chemistry and Pharmacy, 2025)

Staying hooked: effective science engagement and communication in recreational fisheries - Pablo Pita; Sean Tracey; Robert Arlinghaus; Eneko Bachiller; Filipa Pinho-Duarte; Keno Ferter; Filipe Henriques; Samantha Hook; Kieran Hyder; Alejo Irigoyen; María P. Jiménez; Martín Laporta; et al. (Frontiers in Marine Science, 2025)
● This abstract summarizes the results of two expert consultations conducted to gather insights into effective communication and engagement strategies in recreational fisheries. ● Effective science communication fosters knowledge, understanding, and trust in both science and management decisions. ● Public involvement and stakeholder engagement are essential for effective management. ● Simplifying complex research findings and using diverse communication tools enhance awareness and understanding. ● Strong communication strategies are necessary to implement sustainable recreational fisheries management frameworks. ● Funding for communication efforts is often insufficient but remains crucial for success. ● Participatory workshops and data-sharing arrangements enhance collaboration and involvement. ● Multi-stakeholder consortiums and tailored communication strategies strengthen stakeholder engagement and promote adaptive governance. Interdisciplinary outreach and strategic social media use play vital roles in raising environmental awareness.